Targeting corneal disorders using gene therapy. (August 2012) - Parekh, Mohit; Ferrari, Stefano; Di Iorio, Enzo; Barbaro, Vanessa; Bertolin, Marina; Ferrari, Barbara; Ponzin, Diego
The cornea is an extensively studied model for genetic approaches due to its accessibility, transparency, stability, immune privilege and other physiological advantages achievable in both human and animal models. Gene therapy is imminent as a potential measure to treat inherited and acquired diseases of the cornea. Hundreds of experiments have been performed for the detection and identification, delivery, expression and recognition of possible treatments on various corneal disorder models. Viral, nonviral and hybrid vectors, DNA vaccination, RNA interference, enzyme modulation and other approaches have proved to be successful so far. The authors review a quick discussion on the physical, viral, nonviral and other modes of administration of genes, and the effects or challenges posed for treating various corneal disorders.